An option pricing model focus on spread based on the stock price of Eli Lilly and Novo Nordisk - Qian Yuxin (SHS Web of Conferences)
Nowadays, the competition between Eli Lilly and Novo Nordisk is the epitome of the “two-man battle” in the global diet drug and diabetes treatment market. In this study, a European call spread option was designed to accurately capture the competitive dynamics between Eli Lilly and Company (LLY) and Novo Nordisk (NVO) in the GLP-1 diet drug market. By extending the Black-Scholes model and using Monte Carlo simulation, this paper quantifies the impact of spread volatility and correlation on the option value. The empirical results show that the model has flexible hedging and speculation functions in the high-volatility environment of the pharmaceutical industry, but it still needs to combine market expectations to deal with tail risks such as drug safety crises. At the same time, the model optimizes the calculation method of price spread and provides flexible hedging and speculation tools for investors. However, there are still limitations such as the failure to fully predict the disruptive changes of the market and the fact that the historical data may not fully reflect the future market trend.